He Role of Virtual Media in Changing Social Values with an Emphasis on Social Networking Facebook and Telegram - saeed faramarziani; shahnaz hashemi; aliakbar farhangi (توسعه اجتماعی, 2016)
The emergence of social networks, with change in the human interaction, has undergone social values in a dramatic transformation. This study tried to has has evaluated the relationship between utilization of mobile social networking and social values changes, among the youth and middle-aged. This research was conducted by using a survey method. Therefore, 512 people were selected by multi-stage cluster sampling method from two young and middle-aged generations in the five provinces. The data collection instrument was a researcher-made uestionnaire. The results show that there is a relationship between utilization and use of mobile social networking, and intergenerational value difference but in most cases, this is not a positive convergence and has been leading the trend to decrease the tendency of young and middle-aged generations to values of the Iranian society. Also, based on research findings, among both young and middle-aged, there is a significant relationship between the utilization of social networks with social values of individualism, choosing modern clothes, appearance mate selection criteria. But there is a significant inverse relationship. In social values of legalism, religiosity and accountability, ethical standards of mate-selection and selection of traditional clothing.